Comparison of al-Syatibi and Thahir Ibn Asyria’s Thoughts on Maqashid Shari’ah - Bekti Cikita Setiya Ningsih (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2021)
This article will discuss the thoughts of two scholars in the field of maqashid sharia, namely Al-Syatibi as a classical scholar who studied maqashid sharia as an independent discipline until he got the nickname of the first teacher (mu’allim awwal) by producing a work entitled al-Muwaffaqat fi Ushul al-Syariah. The second, Thahir ibn Asyur is a scholar who became the successor of Al-Syatibi in studying the maqashid sharia after the absence of maqashid sharia works for six centuries until he has dubbed the second teacher (mu’allim tsani). According to Al-Syatibi, maqashid sharia is generally divided into two things, namely the legal establishment based on illat (ta’lil problem) and al-mashalih wa al-mafasid (benefit and damage) based on three levels of benefit, namely daruriyyat (primary maslahat), hajiyyat (secondary maslahat), and tahsiniyyat (tertiary maslahat). While Thahir ibn Asyur argues that maqashid sharia is divided into two things, namely maqashid sharia al-ammah and maqashid sharia al-khassah, thahir ibn Asyur’s thinking is based on four things namely: al-musawah, al-fitrah, al-hurriyah and al-samahah. The purpose of this paper is compare the thoughts of the figures regarding maqashid sharia